Digital Humanities: New Tools and New Knowledge - Musgrave, Simon (KnE Social Sciences, 2019)
A key aspect of the rapidly growing field of Digital Humanities is the application of computational tools to problems in humanistic research, a process which can lead to exciting new knowledge. I will illustrate this development with examples from my own research and from that of other scholars showing how the new tools are applicable across many areas of research in the humanities. In particular, I will discuss how the recent development of machine learning algorithms has made it possible to investigate more fully insights based on a theory of meaning (distributional semantics) which is over 60 years old. Although most of my discussion will focus on the application of new methods for research in the humanities, I will end by switching the perspective and considering how such approaches can enrich education in the humanities and produce graduates equipped with diverse skills which will serve them well in our digital world.